2006
DOI: 10.1111/j.1365-2621.2006.tb12395.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Lactobacillus reuteri in Different Types of Microcapsules

Abstract: : This study was designed to find the most suitable method and wall material for microencapsulation of the probiotic bacterium Lactobacillus reuteri to maintain cell viability during gastric challenge. Five L. reuteri strains were individually encapsulated using alginate, alginate plus starch, K‐carrageenan with locust bean gum, or xanthan with gellan by extrusion or phase separation (emulsion). The morphology of the microcapsules was studied using phase contrast and cryo‐scanning electron microscopy (cryo‐SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 24 publications
10
72
0
6
Order By: Relevance
“…The bacteria did not appear on the microcapsule surface, indicating that they were trapped within the matrices. The microstructure of our alginate microcapsules was similar to that of Muthukumarasamy et al (39) and Chen et al (7). Gbassi et al (19) found that probiotic bacteria were randomly distributed in the alginate matrices.…”
Section: Resultssupporting
confidence: 69%
“…The bacteria did not appear on the microcapsule surface, indicating that they were trapped within the matrices. The microstructure of our alginate microcapsules was similar to that of Muthukumarasamy et al (39) and Chen et al (7). Gbassi et al (19) found that probiotic bacteria were randomly distributed in the alginate matrices.…”
Section: Resultssupporting
confidence: 69%
“…Large microspheres can adversely affect the texture of food after supplementation by causing coarseness; small microspheres may not give sufficient protection. Alginate-based microspheres often with between 1.0 to 3.0 mm are obtained, which are too large for many food applications (Sheu and Marshall 1993;Muthukumarasamy et al 2006;Dong et al 2013;Shi et al 2013 a, b). In the present study, alginatewhey protein microspheres were below 1.0 mm.…”
Section: Resultsmentioning
confidence: 99%
“…While the stability of bacterial encapsulated using homogenization and lyophilization process is high, the technology is only suitable for lab scale or pilot-scale experiments because batch sizes are small, and the microcapsule size is relatively large (Muthukumarasamy et al 2006). Spray drying is an alternative encapsulated method that can be conducted in a large scale and has a low cost (Moreau 1991).…”
Section: Introductionmentioning
confidence: 99%